Compliance with good practices for the prescription of medicines in prescriptions attended in the public hospital of Lima - Salvador Ortega, Miriam Janet (2021)
Objective: Identify compliance with Good Prescription Practices for drugs in prescriptions attended at the Public Hospital of Lima. Materials and Methods: Descriptive, cross-sectional and retrospective study. A total of 5,120 prescriptions were reviewed in the period from January to June 2019, verifying compliance with Good Prescription Practices for drugs in prescriptions attended at the Public Hospital of Lima. The SPSS 21.0 program was used in the data analysis. Results: It was identified that the prescriptions issued do not comply with everything stipulated according to the Manual of Good Prescribing Practices of the Ministry of Health of Peru; verifying the following deficiencies: Telephone number of the prescriber or the institution where he works (100%), patient's address (100%), patient telephone number (100%), commercial name of the medicine (100%), dose of the medicine (8 %), pharmaceutical form (71%), therapeutic indications (36%), form of presentation of the prescribed medicine (30%), concentration of the active principle (25%) and legible handwriting (35%). Conclusion: The majority of prescribers do not comply with the manual of good drug prescription practices, which constitute barriers in pharmaceutical care.